Public support for smoke-free private indoor and public outdoor areas in the Netherlands: A trend analysis from 2018– 2022 - Nienke W. Boderie; Sabri Ennissay; Wilhelmina IJzelenberg; Frank J. van Lenthe; Jessica Baars; Jasper V. Been (Tobacco Induced Diseases)
Introduction In addition to smoke-free policies in indoor public and workplaces, governments increasingly implement smoke-free policies at beaches, in parks, playgrounds and private cars (‘novel smoke-free policies’). An important element in the implementation of such policies is public support. In the context of the ambition of the Netherlands to reach a smoke-free generation by 2040, we investigated temporal changes in public support for novel smoke-free policies.